Penyuluhan Hukum Tentang Dampak Pergaulan Bebas Ditinjau Dari Aspek Hukum Perdata Di Kelurahan Punggaluku Kecamatan Laeya Kabupaten Konawe Selatan Sulawesi Tenggara - Deity Yuningsih; Zahrowati Zahrowati; La Ode Muhammad Saleh Saputra (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This Community Service Program is entitled The Legal Ramifications of Permissive Social Behavior. The objective of this program is to enhance public legal awareness and understanding, particularly among adolescents, regarding the consequences of permissive social behavior.The methodology employed in this community service activity comprises lectures and discussions, conducted through direct, in-person engagement with the community, specifically adolescents.Numerous factors contribute to adolescents engaging in permissive social behavior. These factors also elucidate the facility with which they adopt such behavior, often exhibiting a lack of inhibition or shame, whether publicly or among their peers.Specific regulations governing permissive social behavior are not explicitly stipulated in Indonesian Public Law. However, such behavior, when undertaken by adolescents, constitutes a form of deviant behavior that contravenes prevailing moral and religious norms.The factors influencing adolescent engagement in permissive social behavior are categorized as internal and external. Internal factors include age, familial circumstances, deficient self-control, religious adherence, and a diminished sense of shame. External factors encompass the peer group environment, the school environment, economic conditions, as well as the influence of technology and social media.